2017
DOI: 10.9778/cmajo.20160051
|View full text |Cite
|
Sign up to set email alerts
|

Sex and gender considerations in Canadian clinical practice guidelines: a systematic review

Abstract: Background:The importance of sex and gender in the diagnosis and management of health conditions is well established, but the extent to which this evidence is integrated into clinical practice guidelines remains unknown. We aimed to determine the proportion of Canadian clinical practice guidelines that integrate evidence on sex and gender considerations. Methods:We searched the Canadian Medical Association's CPG Infobase, PubMed, all provincial/territorial websites and websites of professional organizations fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 79 publications
1
64
0
5
Order By: Relevance
“…Despite a general understanding that appearances and outcomes of diseases may contrast for male and female patients, the uptake of sex and gender factors into CPGs has been slow, with only 20% of CPGs recommending sex-specific diagnostic or treatment strategies. 35,36 Tannenbaum et al offer a number of clinical examples in which the consequences of not including evidence separately in CPGs about women and men can range from missed opportunities to incorrect prescription of drugs. 5 If quality of care for both male and female patients is to be enhanced, sex and gender differences must be incorporated into CPG development.…”
Section: Clinical Practice Guidelines For Women With Cvdmentioning
confidence: 99%
“…Despite a general understanding that appearances and outcomes of diseases may contrast for male and female patients, the uptake of sex and gender factors into CPGs has been slow, with only 20% of CPGs recommending sex-specific diagnostic or treatment strategies. 35,36 Tannenbaum et al offer a number of clinical examples in which the consequences of not including evidence separately in CPGs about women and men can range from missed opportunities to incorrect prescription of drugs. 5 If quality of care for both male and female patients is to be enhanced, sex and gender differences must be incorporated into CPG development.…”
Section: Clinical Practice Guidelines For Women With Cvdmentioning
confidence: 99%
“…Yet a 2017 review suggested that only 35% of Canadian practice guidelines reported screening, diagnosis or management considerations specific to sex or gender, and only 25% used the terms "sex" and "gender" correctly (Tannenbaum et al 2017). Research results still need to be translated into practice.…”
Section: Addressing the Gapsmentioning
confidence: 99%
“…In addition, the project will also contribute to the science of reporting guidelines as it will be among the first to integrate sex and gender considerations. The rationale of taking into account sex and gender in the development of the reporting guideline stems from several elements: while their importance in the manifestation and management of health conditions and in health outcomes is now getting better established, their considerations are rarely integrated in research design and reporting guidelines [24,25]; importance of appropriate use of the terms sex and gender based on documentation that they are often misused, misunderstood, confused, or conflated in health research [26], unlike other health determinants such as education, employment, and income; and fulfillment of the role of a reporting guideline that is to help reduce waste in health research by addressing the deficiency in the quality of its reporting and better inform practice, policy, and programs. Moreover, the success of implementation and scaling is highly context-dependent, particularly for complex interventions.…”
Section: Introductionmentioning
confidence: 99%